Efisiensi Serapan Nitrogen pada Pertumbuhan Kacang Panjang (Vigna sinensis L.) setelah Pemberian Sludge Industri Karet Remah - Abdul Hafiz; Sasi Gendro Sari; Chatimatun Nisa (Bioscientiae, 2020)
The availability of industrial crumb rubber sludge at PT. Bumi Jaya is quite much (1 ton/4 months), but it has underutilized optimally. High nitrogen content in industrial crumb rubber sludge has the potential to be used as an alternative nitrogen fertilizer, but keep in mind that an efficient use of appropriate plants need nitrogen uptake value in the plant tissue. This research aimed to determine the benefit or potential of industrial crumb rubber sludge as the nitrogen fertilizer alternative with measuring the nitrogen uptake efficiency on the growth of cowpea. The research was done from October to November 2016 in the greenhouse of basic laboratory of Lambung Mangkurat University. Sludge dose which was used in fertilizer were 60 g, 120 grams and 180 g/5 kg or equivalent dose of 10 ton/ha. The observed variables include nitrogen uptake efficiency, the soil C/N ratio and growth of cowpea plant on day 15th, 30th, and 45th after planting. On day 45th the plant was harvested and then fresh weight, dry weight, number of root nodules, plant tissue N of cowpea and soil C/N ratio were measured. The results showed that the efficiency of nitrogen uptake and growth observation variables of cowpea were optimum on sludge dose of 120 grams compared to the other doses. Sludge dose of 120 grams showed the best C/N ratio (12.04) among the other treatments.